Assuring Timeliness in an e-Science Service-Oriented Architecture. - Sloan, John C.; Khoshgoftaar, Taghi M.; Raghav, Venkat (Computer (00189162), 2008)
The article discusses public-resource computing, examining the role of service-oriented architecture (SOA) in coordinating the timely delivery of a volunteer's computing power with the scientific community's corresponding needs. Topics include coordination and deployment issues, inbound and outbound processes, intricate workflow resolution, and provider problems. Also discussed are the complex decision-making matrices faced by volunteer supercomputing portals and the use of a simplified version of the Berkeley Open Infrastructure for Network Computing (Boinc).